Recent progress in metabolomics for analyzing common infertility conditions that affect ovarian function - Hiroshi Kobayashi; Shogo Imanaka (Reproductive Medicine and Biology)
Abstract Background Numerous efforts have been undertaken to identify biomarkers associated with embryo and oocyte quality to improve the success rate of in vitro fertilization. Metabolomics has gained traction for its ability to detect dynamic biological changes in real time and provide comprehensive metabolite profiles. This review synthesizes the most recent findings on metabolomic analysis of follicular fluid (FF) in clinical conditions leading to infertility, with a focus on the dynamics of energy metabolism and oocyte quality, and discusses future research directions. Methods A literature search was conducted without time constraints. Main findings The metabolites present in FF originate from five primary pathways: glycolysis, oxidative phosphorylation, lipid metabolism and β‐oxidation, nucleic acid synthesis, and ketogenesis. Metabolomic profiling can broadly categorize infertile women into two groups: those with infertility due to aging and endometriosis, and those with infertility associated with polycystic ovarian syndrome and obesity. In the former group, glycolysis and lipid metabolism are upregulated to compensate for mitochondrial dysfunction, whereas the latter group exhibits the opposite trend. Assessing the levels of glucose, pyruvate, lactate, and plasmalogens in FF may be valuable for evaluating oocyte quality. Conclusion Metabolomic analysis, particularly focusing on energy metabolism in FF, holds promise for predicting female reproductive outcomes.